Wind energy's bycatch: Offshore wind deployment impacts on hydropower operation and migratory fish. (June 2021) - Pfeiffer, Olivia; Nock, Destenie; Baker, Erin
Abstract: Hydropower plays a key role in maintaining grid reliability, but there is uncertainty regarding the ecological implications of using hydropower to balance variability from high penetration of intermittent renewable resources, such as solar and wind. Hydropower can offer advantages at the macro-ecological level ( e.g., reduced greenhouse gas emissions), however it may have significant environmental impact on a local level ( e.g., increased risk to fish species during migration and breeding periods). Using the New England region as a case study, we use an electricity model to estimate how hydropower operation changes as offshore wind capacity increases at a system level. We then tie alterations in hydropower energy production to local impacts on riverine ecosystems and the lifecycle of migratory fish. We find that increasing offshore wind capacity from 1600 to 10, 000 MW more than doubles the average hourly hydropower ramping need and the associated river flowrate during April. This increased flowrate aligns with the migration timing of the lone endangered fish species on the Connecticut River, the shortnose sturgeon. Alternatively, the majority of months in which hydropower operation is most strongly impacted by the addition of offshore wind capacity do not coincide with key fish lifecycle events. Other sustainability benefits, including reduced air pollution and water consumption, can be achieved through deployments of offshore wind. Our results suggest that in order to balance global ( i.e., CO2 mitigation) and local ( i.e., fish migration) environmental issues, a portfolio of solutions is needed to address grid integration of renewables. Highlights: We develop a model for estimating the impact of wind energy on hydropower generation needs. We develop an energy system model to connect system level energy changes to fish migration patterns. Wind energy impacts on hydropower operation fluctuations are linked to changes in river flows and impact on fish. Increased flowrates align with the migration timing of endangered fish species on the Connecticut River. Sustainability assessment shows increased wind would reduce water consumption and air pollution emissions.